Prevalence and molecular pathogenic markers of mycoplasma gallisepticum infection in commercial chickens and progenies - Ahmed, Zahraa Faisal (2011)
Mycoplasma gallisepticum (MG) causes chronic respiratory disease and the infection is very costly to the poultry industry. There are few published data on avian mycoplasmosis and there is no report on molecular pathogenicity of MG infection in Malaysia. Therefore, this study was carried out to determine the prevalence of MG, and the molecular pathogenic markers of MG infection in the commercial chickens and their progenies (pipped embryos, normal chicks and poor quality chicks), in order to understand the molecular level of pathogenicity. The prevalence of MG infection in chickens was determined in selected commercial farms (breeder, broiler and layer) and the progenies [pipped embryos (PE), day old poor quality chicks (PQC) and normal chicks (NC)]. All samples were obtained from farms in Peninsular Malaysia. A total of 3056 swab samples were collected of which 1243 are from pipped embryos, 248 from day-old poor quality chicks, 340 from day- old normal chicks and 1225 from adult commercial chickens. Conventional polymerase chain reaction (PCR) test was performed using specific gene target sequence and encoding the surface protein for detection of MG directly from the clinical samples without prior isolation of the target MG. The primer used was designed to bind to the Adherence protein A gene (gapA) and amplify a 505 bp DNA fragment. In this study, 571 positive samples of MG out of 3056 samples with overall prevalence of 18.68% were detected from different progenies and adult commercial chickens. The total prevalence rates were 13.7 % in the pipped embryos, 16.9 % in the poor quality chicks, 12.6% in the normal chicks, and 25.8% in the adult commercial chickens. This study shows the high prevalence of MG infection through vertical and horizontal transmission from many geographically distinct areas of the country, although these farms have vaccination and treatment history. The present study demonstrated that the control of MG was not successful, despite the use of live and /or killed MG vaccines, an extensive medication program and strict biosecurity. These positive MG samples were used for molecular characterization by amplification of selected gene target specific sequences to MG, hemagglutinin protein A gene (pMGA) and Phase-variable putative adhesin protein A gene( pvpA), using conventional PCR of published sequence specific primers. These two genes, pMGA and pvpA genes have gene size polymorphism on specific target sequence. The PCR results demonstrated, a total of 281 MG positive field samples out of 571 MG samples were detected with the primer targeted pMGA gene and a total of 188 MG positive field samples out of 571 MG samples were detected with the primer targeted pvpA gene. Similar and identical banding patterns were observed among MG positive samples obtained from progenies, however there was a variable on the banding pattern among MG positive samples obtained from adult commercial chickens using the agarose gel electrophoresis. The sequencing and phylogenic analysis results of MG based on selected genes targeted specific sequences were obtained using Bioinformatics software (Bioedit and MEGA 4. software). The characteristics of the positive MG field positive samples were determined. The genetic diversity of the pMGA and pvpA genes of MG positive samples originated from adult commercial chickens and progenies were investigated. In the present study, we evaluated the genetic variability of 77 field positive samples of MG using the pMGA gene and 49 field positive samples of MG using the pvpA gene, detected in progenies and adult commercial chickens and compared them to the reference and vaccine strains of MG obtained in this study. Genetic variation patterns were evaluated by partial nucleotide sequencing of the pMGA and pvpA genes, which encode putative cytadhesion proteins. The gene size variation patterns of the pMGA and pvpA genes among MG field positive samples shared identical gene size variation patterns with the pathogenic reference and vaccine strains, that is, an insertion bp fragments by using the pMGA gene primer set and a deletion bp fragments by using the pvpA gene primer set. Therefore, it showed that there was identical genes size variation patterns of the MG positive samples with the pathogenic reference and vaccine strains which are pathogenic by nature and can be transmitted vertically. However, the gene size variation patterns are quite different from the variation pattern of the less pathogenic vaccine strain that cannot be transmitted vertically.This study concluded the identification of two amplification based genetic markers that highly correlate with the existing pathogenicity studies of MG infection. It also proved the importance of these two primer sets and showed that the primer of pMGA gene might be considered as a vertical genetic marker, and the gene size polymorphism patterns by both of selected primer sets of the pMGA and pvpA genes might be considered as potential pathogenic molecular markers. The present study proved the ability of both selected primer sets of the pMGA and pvpA genes in differentiating avirulent ts11 strain and virulent reference strains. Therefore both these selected primer sets are good pathogenic markers of MG that can be used to differentiate whether the MG field strains are pathogenic or less pathogenic.